Analysis of Dither in PWM Control on Electro-hydraulic Proportional Valve - Guoping LIU; Wuxing XIA; Dawei QI; Ronghua HU (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Plus with modulation (PWM) is widely used in proporational control systems for it is efficient, flexible and anti-interference. Due to the friction and hysteresis of electromagnet, hysteresis exists when hydraulic valve in steady-state, and hysteresis influences the dynamic characteristics of the valve seriously,the hysteresis can be improved by superimposing dithers with certain frequency and amplitude to the valve coil. Aiming at the character of anti-unloading power driver circuit ,this paper analyzed the parasitic dither which exists in ±24V PWM control，besides，the experiment shows that in a high frequency PWM, dither with independent frequency and amplitude can be generated by changing the frequency of the PWM, in this way, the dithers  and average current of coil  can be adjusted separately by changing PWM frequency and PWM duty cycle. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3698